Liquid–liquid phase separation drives the β‐catenin destruction complex formation - Shi, Qiaoni; Kang, Kexin; Chen, Ye‐Guang (BioEssays, 2021)
The intracellular multiprotein complex β‐catenin destruction complex plays a key role in Wnt/β‐catenin signaling. Wnt stimulation induces the assembly of the receptor‐associated signalosome and the inactivation of the destruction complex, leading to β‐catenin accumulation and transcriptional activation of the target genes. The core components of the destruction complex include Axin, APC, GSK3β, CK1α and other proteins. Recent studies demonstrated that Axin and APC undergo liquid–liquid phase separation (LLPS), which is critical for their function to regulate Wnt/β‐catenin signaling. Here, we discuss the possible roles of LLPS in Wnt/β‐catenin signaling and regulation of Axin LLPS by post‐translational modifications. The formation of the destruction complex is driven by IDR1‐mediated Axin1 LLPS, which is promoted by APC LLPS. In addition, β‐catenin has been reported to undergo LLPS in the nucleus. It remains unclear whether Dvl go through LLPS and its effect on the destruction complex.